2018
DOI: 10.1155/2018/4851512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Treatment, and Associated Factors of Hypertension in Spain: A Comparative Study between Populations

Abstract: The prevalence and related factors of hypertensive subjects according to the resident area (rural versus urban) were investigated in two population-based studies from Spain. Medical questionnaires were administered and anthropometrics were measured, using standardized protocols. Hypertension was diagnosed in pharmacology treated subjects or those with blood pressure (BP) ≥140/90 mm Hg. Regarding BP control, it was defined as under control if BP was <140/90 or <140/85 mm Hg in type 2 diabetic subjects. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…The present study highlights that alcohol intake, cigarette smoking, and obesity may increase the risk of hypertension in Xinjiang residents, consistent with previous literatures [2528]. Most importantly, alcohol intake, compared to nondrinkers, was significantly related to increased prevalence of hypertension by 3.9 folds.…”
Section: Discussionsupporting
confidence: 92%
“…The present study highlights that alcohol intake, cigarette smoking, and obesity may increase the risk of hypertension in Xinjiang residents, consistent with previous literatures [2528]. Most importantly, alcohol intake, compared to nondrinkers, was significantly related to increased prevalence of hypertension by 3.9 folds.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also showed an important relationship of hypertension risk development with epidemiological data as male gender, age over 65 years, be pensioned, living in a rural area, lower educational level, and low income. These results completed the role described by other authors about the social determinants in the development of hypertension and BP control ( 12 , 26 ).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, a higher education level among the healthy group was detected, and twice, unemployed/retired were found in the diseased group, which may be due to older aged subjects in this category. Data collection has some influence since hypertension rates in the current cohort were lower than data provided by other studies [ 42 , 43 ]. Indeed, in an online population, it may be found that only those with antihypertension treatment may respond as suffering cardiometabolic manifestation, which also applies for the diabetes, obesity and dyslipidemia questions/answers.…”
Section: Discussionmentioning
confidence: 82%